Biedni Polacy patrzą na warszawskich Żydów i na getto warszawskie - Grabowski, Jan (Zagłada Żydów. Studia i Materiały, 2014)
The article presents a series of excerpts from various diaries written by Polish writers, who either visited the Warsaw Ghetto, or had a chance to observe the tragedy of Warsaw’s Jews from behind the ghetto walls.